Local community participatory process and intervention procedure in mangroves ecotourism of Marudu Bay, Sabah - M., Abdullah; Abd. Ghani, Awang Noor; Ibrahim, Faridah Hanum; Zakaria, Muta Harah; Hin, Wai Yip (Universiti Putra Malaysia Press, 2013)
Mangrove forest extensively colonizes the coastal front of Malaysia, including Sabah state of Northern Borneo. In Marudu Bay in Sabah, it was not harnessed by local communities for ecotourism purposes to complement their incomes mainly from fishing activities. The objective of study was to assess local community`s participation in mangrove ecotourism and the intervention procedure needed for success of such a project. The method involved stakeholder analysis using three consultation workshops comprising of key informants and selected villagers as primary stakeholders. Focus Group Discussion (FGD) was followed to elicit responses on ecotourism development within the locals` surroundings and impacts in their daily lives and future undertakings. Results from stakeholder analysis showed that the local communities have the urgency to participate in ecotourism as a new opportunity while supporting mangroves protection. In fact, most of them were found to be willing to provide the services needed to protect the mangrove ecosystem. The intervention needed included support for business activity including ecotourism products and activities development, identification of local leadership/players to spearhead the activities, technology transfer such as technical and facilities assistance, and human capacity building. As for sustainable endeavour, collaborations with big and successful tourism players are crucial to bring their clients to the site as extended visit.